Impact of Good Governance on Domestic Investment: Empirical Study for Pakistan - Muhammad Khalid; Alam Khan; Ihtisham ul Haq; Shahid Munir; Hassan Taj (International Journal of Business and Economic Affairs, 2023)
Governance is a procedure of endeavoring basic leadership and implementations. It is a tool of managing national affairs through economic, political and administrative perspectives. Good Governance refers to the effective and efficient working of state machinery. In recent times good governance is considered as a key indicator that can empowers a country’s economic health. The current study aims to assess the impact of good governance on domestic investment in case of Pakistan by using time series data. All the series are tested for the unit root through Augmented Dicky-Fuller (ADF) and Phillips-Peron (PP) tests. The ADF and PP tests shows that variables are integrated at first difference. The study employed co-integration techniques such as Johanson co-integration to find the long-run co-integration among variables. Furthermore, the long run coefficients of the variables the study employed the fully modified least square. The results shows that control of corruption, government effectiveness, voice and accountability and regularity quality have significant positive impact on domestic investment. It is suggested that government has to work on good governance to encourage domestic investment to sustain sound and long term economic growth.